Nociceptive sensitizers are regulated in damaged joint tissues, including the articular cartilage, when osteoarthritic mice display pain behaviour - Driscoll, C; Chanalaris, A; Knights, C; Ismail, H; Sacitharan, P; Gentry, C; Bevan, S; Vincent, A (Wiley, 2015)
Objective: Pain is the most common symptom of osteoarthritis yet where it originates in the joint and how it is driven is unknown. Methods: 10 week old mice underwent sham surgery or surgical joint destabilization by either partial meniscectomy (PMNX) or by destabilizing the medial meniscus (DMM). Pain-related behavior, by a variety of methods (von Frey, cold plate sensitivity, analgesimeter, incapacitance testing, forced flexion) was assessed weekly. Once pain-related behavior was established, RNA was extracted from either whole joints or micro-dissected tissues (articular cartilage, meniscus, bone). RT-PCR was carried out for 54 genes known to regulate pain sensitization. Cartilage injury assays were performed using avulsed immature murine hips from wild type or genetically modified animals, or by explanting articular cartilage from porcine joints pre-injected with pharmacological inhibitors. NGF protein was measured by ELISA. Results: Mice developed pain-related behavior 8 weeks following PMNX or 12 weeks following DMM. Nerve growth factor, bradykinin receptors B1 and B2, tachykinin and its receptor, were significantly regulated in the joints of mice displaying pain-related behavior. There was little regulation of inflammatory cytokines, leukocyte activation markers or chemokines. When tissues were analysed separately, NGF was consistently regulated in the articular cartilage. The other pain sensitizers were also largely regulated in the articular cartilage although there were some differences between the two models. Nerve growth factor and tachykinin were strongly regulated by simple mechanical injury of cartilage in vitro in a TAK1, FGF2 and Src kinase dependent manner. Conclusion: Damaged joint tissues produce pro-algesic molecules including NGF in murine OA. This article is protected by copyright. All rights reserved.